(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Ultraviolet-visible (UV-VIS) spectrophotometry is a cost effective, reliable and less time-consuming analytical technique used for the quantitative analysis, to detect the presence of impurities, chemical deterioration, and impact of stabilizers and packaging material in the pharmaceutical products. The absorbed spectrum dictates about the microscopic environments in the samples. Objectives: The research developed and validated a simple, easy, precise, and robust quantitative analytical technique for Swertiamarin (SWMN) according to ICH criteria. Results: The results showcased that the absorption spectrums of Swertiamarin in the UV overlay at λmax 236 nm at 4 to 32 μg/ml. and linear at each concentration. Within the range of 98.5 to 104.6, the % recovery was seen. The sensitivity of the method was observed at the concentrations 0.163µg/ml (LOD) and 0.493µg/ml (LOQ). Conclusion: Precision, repeatability, accuracy, ruggedness, and robustness were well within limitations. Quantitative UV spectrophotometry can determine a sample's (SWMN) concentration for routine analysis.